Physical, mechanical, and anatomical properties of 12 jabon (Neolamarckia cadamba) provenances wood in Indonesia - NELLY ANNA; ISKANDAR Z. SIREGAR; SUPRIYANTO SUPRIYANTO; DEDE J. SUDRAJAT; LINA KARLINASARI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Anna N, Siregar IZ, Supriyanto, Sudrajat DJ, Karlinasari L. 2023. Physical, mechanical, and anatomical properties of 12 jabon (Neolamarckia cadamba) provenances wood in Indonesia. Biodiversitas 24: 5895-5904. Jabon is a raw wood material for paper industries and has a fast-growing ability. Comprehensive information on the fundamental qualities of wood from the 12 provenances of jabon (Neolamarckia cadamba (Roxb.) Bosser) is a critical aspect of understanding their superior properties. The age of the samples at the trial was 42 months old, and the number of trees tested was 12, representing one provenance. Wood samples for physical (disk samples), mechanical, and anatomical properties were sampled at a height and length of 1.3 m and 35 cm. The logs were divided into 5 cm and 30 cm for wood samples with anatomical and mechanical properties. The physical and mechanical properties were tested according to ASTM D 4442, ASTM D 2395, and ASTM D 143 standards. The physical (density, specific gravity, and moisture content), mechanical properties (MOE and MOR), and anatomical properties (fiber length and microfibril angle) were carried out on wood from 12 provenances. Physical and anatomical properties were tested, from the pith to the outer bark. The average green wood density was 0.94 gcm-3, while the highest was obtained in the Rimbo Panti, Nusakambangan, Kapuas Tengah, and Batu Hijau provenances. The average specific gravity value from the 12 provenances of jabon was 0.46 in Batu Licin and Batu Hijau provenances; the average moisture content on oven-dry weight was 105.13%; and the highest value was in the Kuala Kencana provenance. The average MOE and MOR values were 51,039.93 kgcm-² and 488.37 kgcm-², with a dry air moisture content of 13.62%. The highest MOE and MOR values were in the Batu Licin and Gowa provenance, with MFA testing varied at 11.54°. The fiber length from the pith to the outer bark tended to increase, with an average of 1183.28 ?m. Based on the value of physical, mechanical, and anatomical properties, 12 provenances of jabon can only be used as non-structural raw materials. The Batu Hijau provenances have the highest density and specific gravity. However, the highest fiber length was found in Gowa provenance.